Repetitive Transcranial Magnetic Stimulation Induces Quantified Functional and Structural Changes in Subcortical Stroke: A Combined Arterial Spin Labeling Perfusion and Diffusion Tensor Imaging Study - Jin, Yu; Bai, Xi; Jiang, Binghu; Guo, Zhiwei; Mu, Qiwen (Frontiers in Human Neuroscience, 2022)
Purpose: To explore the changes of cerebral blood flow (CBF) and fractional anisotropy (FA) in stroke patients with motor dysfunction after repetitive transcranial magnetic stimulation (rTMS) treatment, and to better understand the role of rTMS on motor rehabilitation of subcortical stroke patients from the perfusion and structural level. Material and methods: Twenty-three first-episode acute ischemic stroke patients and sixteen healthy controls (HCs) were included. The patients were divided into rTMS and sham group. The rehabilitation assessments and examination of perfusion and structural MRI were performed before and after rTMS therapy for each patient. Voxel-based analysis was used to detect the difference in CBF and FA between three groups. The Pearson correlation analysis was conducted to evaluate the relationship between the CBF/FA value and the motor scales. Results: After rTMS, significantly increased CBF were found in the ipsilesional supplementary motor area, postcentral gyrus, precentral gyrus, pons, Medulla Oblongata, contralesional midbrain, superior cerebellar peduncle, and middle cerebellar peduncle than pre-stimulation and sham group, these fasciculi comprise the cortex-pontine-cerebellum-cortex (CPC) loop. Besides, altered CBF in ipsilesional precentral gyrus, postcentral gyrus and pons were positively associated with improvement of FMA scores. Significantly decreased FA was found in the contralesional precentral gyrus, increased FA was found in the ipsilesional postcentral gyrus, precentral gyrus, contrlesional supplementary motor area and bilateral cerebellum, these fasciculi comprise the corticospinal tract (CST). The change of FMA score was positively correlated with altered FA value in the ipsilesional postcentral gyrus and negatively correlated with altered FA value in the contralesional precentral gyrus. Conclusion: Our results suggest that rTMS could facilitate the motor recovery of stroke patients. High-frequency could promote the improvement of functional activity of ipsilesional CPC loop and the recovery of microstructure of CST.